Investigation of LiMo3Se3 nanowires, nanowire networks and ion-exchanged X+ {Mo3Se3}- networks - Sheridan, John Gerard (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
With the limits of current silicon processing techniques drawing nearer, the "bottom up" approach for future technologies has become a focus of major research worldwide. This requires detailed studies of possible replacement materials for interconnects and the active components of nanoscale devices. To this end we present results for the inorganic nanowire system, Li+ {Mo3Se3}- and of its ion exchanged network counterparts, X+ {Mo3Se3}-, by a variety of techniques, including Scanning Transmission Electron Microscopy (STEM) and its associated spectroscopies. Atomic Force Microscopy (AFM), rheology and dynamic light scattering of solutions.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.